Does English proficiency affect academic performance?. (May 2018) - Geide-Stevenson, Doris
Abstract: Based on data from international transfer students in a dual degree undergraduate economics program in the U.S., this research asks whether English proficiency impacts academic performance measured as the overall U.S. GPA upon graduation and the grade obtained in a writing-intensive capstone course. The results indicate that English proficiency positively impacts academic performance, but at a declining rate. This non-linear relationship is sensitive to whether students placed into an English as a Second Language program are included in the sample or not and the type of achievement variable considered, thus highlighting a more nuanced result than expected.